The Liver of the Aquacultured Japanese Pufferfish(1)()) (Natural Toxins) (Food Saf (Tokyo), 2017)
Pufferfish is categorized as one of foods which contain or are covered with toxic or harmful substances or are suspected to contain or be covered with such substances” in Article 6, Item (ii) of the Food Sanitation Act (Act No. 233 of December 24, 1947). The issue, however, stipulates in the proviso “that this shall not apply to cases where the Minister of Health, Labour and Welfare (MHLW) specifies that such articles involve no risk to human health”. Based on the proviso, the pufferfish species and the edible parts, which involve no risk to human health, were specified in the notice titled “New Rules for Measures to Secure Sanitation Regarding Pufferfish”. Currently, the liver of Japanese pufferfish (Takifugu rubripes, hereinafter referred to as “Torafugu”) is not included in the notice, thus shall not be sold based on Article 6, Item (ii) of the Act. A proposal to add the liver of Torafugu as a food which involves no risk to human health, as one of the cases stipulated in the proviso, was submitted to the MHLW. In response to the request from MHLW, Food Safety Commission of Japan (FSCJ) conducted a risk assessment on the liver of Torafugu that is aquacultured and served to the customer under the controlled procedures proposed by Saga prefecture and a business operator in the prefecture (hereinafter referred to as “the specified operator”). The proposed procedures are: 1) Torafugu is aquacultured on land under the control of the specified operator. 2) Using a HPLC-FL method, TTX level of a part of liver tissue from every Torafugu fish is determined. 3) Only the liver showing below the detection limit of TTX will be served exclusively in the restaurants managed by the specified operator. FSCJ conducted the risk assessment mainly from the view points; 1) toxificating mechanisms of Torafugu, as well as hazards and risk control points in the on-land aquaculture, 2) validity of the HPLC-FL method for TTX analysis, 3) reliability of the sampling part for TTX-level determination, 4) acceptability of exclusive determination of TTX. Based on the current findings and data in the documents submitted, FSCJ concluded that the safety of the liver of Torafugu aquacultured on land through the proposed procedures could not be secured, even with the determination of TTX in the individual liver.